Agrarian Law Study on the Settlement of Customary Land Disputes in Sorong Regency - Aru , Demianus; Markus, Dwi Pratiwi; Yati, Sri; Simanjuntak , Kristi Warista (Academos, 2024)
Land is considered very important for human life that needs to be maintained. Land law in Indonesia has been regulated in Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles (UUPA), which means that it is a whole of written and unwritten legal norms. Land is not only a place to stand, but also a place for the growth of natural resources, habitat for various types of living things, as well as the foundation for economic and social development, not infrequently this causes a problem or conflict. This research aims to find out the existence of agrarian law in solving customary land problems in Sorong Regency. This research uses a socioligical juridical approach method to examine the problems studied. The results of this study indicate that Agrarian Law becomes the basis for resolving customary land issues in Sorong Regency without overriding Customary Law and Customary Law that already exists in the community in Sorong Regency.